2013
DOI: 10.4172/jmso.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Parity Associated with Long-Term Disease Progression in Women with Multiple Sclerosis

Abstract: Background: Pregnancy in multiple sclerosis (MS) is marked by a decrease in relapse activity with a corresponding rebound in the first months postpartum. Because MS typically occurs during childbearing years, it is important to determine the long term effect of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…here is general agreement that pregnancy does not influence disability or progression in women with multiple sclerosis (MS) [1][2][3][4] and some evidence that it confers a favorable long-term prognosis. 5 Despite the fact that pregnancy is no longer discouraged, none of the current disease-modifying therapies (DMTs) is approved for use during pregnancy. Thus, treatment is typically discontinued on confirmation of an unintended pregnancy or when a woman is trying to conceive.…”
mentioning
confidence: 99%
“…here is general agreement that pregnancy does not influence disability or progression in women with multiple sclerosis (MS) [1][2][3][4] and some evidence that it confers a favorable long-term prognosis. 5 Despite the fact that pregnancy is no longer discouraged, none of the current disease-modifying therapies (DMTs) is approved for use during pregnancy. Thus, treatment is typically discontinued on confirmation of an unintended pregnancy or when a woman is trying to conceive.…”
mentioning
confidence: 99%
“…Our data hamper us in confirming previous evidence that number of pregnancies may convey a favorable disability prognosis in MS [ 14 , 15 , 16 ]. Previous studies have been conducted to investigate the role of pregnancy on disability progression, supporting that parous wwMS had a lower risk than nulliparous wwMS in reaching EDSS 4.0 and 6.0 [ 10 , 12 , 17 ]. To our knowledge, this is the first study conducted to evaluate whether, within “parous” wwMS, the number of pregnancies (“offspring number”) could be associated with the long-term disability status.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction of relapses during pregnancy (70% in the last trimester) was observed, with a sharp rebound to 70% above pre-pregnancy relapse rates during the first three months postpartum [ 3 , 4 ]. Recently, Teter et al [ 12 ] showed that during a mean follow-up period of 5.6 years after delivery, the parous wwMS take a longer time to reach a disability milestone (the use of a cane, EDSS of 6.0). However, other studies showed no effect of parity on disability, even if the follow-up periods tended to be inconsistent or too short (3–12 months postpartum) [ 10 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations